Lewis Foreman, Bax: A Composer and His Times, third edition (2007) - Huss, Fabian (Journal of the Society for Musicology in Ireland, 2007)
A review of Lewis Foreman, Bax: A Composer and His Times, third edition (Woodbridge: Boydell Press, 2007), ISBN 978-1-84383-209-6, 616pp, £29.95/$55.